Проблемы экономики. О структуре общества Ближнего Востока до середины II тыс. До. н.э. (3. Структура общинного сектора экономики в Западной Азии) - Дьяконов, И. M.
D’jakonov = Diakonoff, I. M.; Problems of Economics. The Structure of Near Eastern Society to the Middle of the Second Millennium B.C. (3. The Structure of the Communal Sector of the Economy in Western Asia); 1. und 2. vgl. VDI 4/1967, 13-35 = 794. — engl. Résumé.